Enhancing Primary Healthcare Infrastructure under Vision 2030: Strategic Development of Medical Clinics in Saudi Arabia - Alshehri, Hamdan Ahmed Hamdan; Alahmadi, Asmaa; Altarjami, Amer; Almohsen, Nasser; Alyahyawi, Nawaf Othman Ahmed; Alharbi, Abdulaziz Muhammad; Alahmade, Muhannad; Alharbi, Amjad Majed (Journal of Posthumanism, 2024)
Saudi Arabia’s Vision 2030 has prioritized healthcare transformation through the expansion and modernization of primary healthcare clinics (PHCs) to ensure equitable access, high-quality services, and patient-centered care. This review explores strategic approaches to developing medical clinics within this national framework. It synthesizes literature from 2016–2025 on healthcare infrastructure, digital transformation, public-private partnerships (PPPs), and workforce development in Saudi Arabia. The findings highlight that effective clinic development depends on integrating smart health technologies (EHR, telemedicine), optimizing clinic design for patient flow, and empowering multidisciplinary teams. Policy reforms under Vision 2030—such as corporatization of health clusters, privatization initiatives, and value-based healthcare—have accelerated the establishment of resilient, efficient, and technologically enabled clinics. Challenges remain in rural accessibility, data interoperability, and workforce readiness. The review concludes with strategic recommendations for sustainable clinic development through innovation, digital integration, and human capital investment.